Hormonal, metabolic, and skeletal muscle adaptations following weight loss: effect of dietary fat type - Calsbeek, Dean Joseph, author (Colorado State University. Libraries, 2003)
These studies investigated the effect of dietary weight-loss and a specific dietary fat type, ALA(18:3n-3), on the hormones leptin and insulin and the peroxisome proliferator activated receptor (PPAR) family of nuclear receptors in the skeletal muscle of obese humans. It was hypothesized that a 10% weight-loss induced by a hypocaloric diet would result in decreased protein concentrations of PPARα and PPARβ but increased protein concentrations of PPARγ, but dietary supplementation with ALA(18:3n-3) would diminish this effect. Furthermore, it was hypothesized that plasma concentrations of leptin and insulin would decrease with weight loss, but that ALA(18:3n-3 supplementation would also reduce this effect. All subjects were prescribed hypocaloric diets at 80% of resting metabolic rate until 10% weight-loss was achieved. In addition, a subset of subjects exchanged some of their dietary fat with a flaxseed oil capsule supplement (~60% ALA(18:3n-3)) thereby increasing the dietary intake of ALA(18:3n-3) from a typical 0.5% of total caloric intake (control group) to 5% of total caloric intake (ALA group). The dietary composition of the group diets were significantly different for ALA(18:3n-3). This difference was reflected in erythrocyte membrane fatty acid composition, as flaxseed oil supplemented subjects experienced a significant increase of ALA(18:3n-3) composition in the erythrocyte membranes. Muscle biopsies were taken before and after weight-loss in both groups. Western blots for PPAR isoforms showed that PPARβ significantly increased with dietary weight-loss. The effect of weight-loss was reversed, however, in subjects supplemented with ALA(18:3n-3). A similar, but non-significant trend was seen for PPARα, and the opposite effect (also nonsignificant) was observed for PPARγ. These observations indicate that skeletal muscle concentrations of the PPAR isoform proteins fluctuate to reflect the metabolic state of the tissue rather than to protect the tissue from energy deprivation, as hypothesized. These changes, however, may be negated by supplementing the diet with ALA(18:3n-3). Plasma concentrations of leptin and insulin decreased significantly for both groups, but there was no effect of ALA(18:3n-3) supplementation for either hormone. These findings may be important in future treatment of obesity. The significance and relationship of these observations is discussed, in addition to ideas for future research.
Keywords: nutrition